A new routing algorithm for symmetric rearrangeable networks and emerging applications - Chakrabarty, Amitabha; Collier, Martin J. (© 2012 IEEE, 2016)
This conference paper was presented in the International Conference on Advanced Computer Science Applications and Technologies, ACSAT 2012; Kuala Lumpur; Malaysia; 26 November 2012 through 28 November 2012 [© 2012 IEEE] The conference paper's definite version is available at: :http://dx.doi.org/10.1109/CICN.2012.25